1985
DOI: 10.1002/j.1556-6978.1985.tb00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Group Supervision: Widely Practiced But Poorly Understood

Abstract: The group supervision literature in counselor training from 1960 to 1983 was reviewed. Only those articles pertaining to supervised groups of counselor trainees participating in individual counseling practica were included. Descriptions of group supervision included elements of case presentation, didactic information, and interpersonal process. Because of the paucity of research in group supervision, practices are based on intuitive common sense approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
88
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 30 publications
(29 reference statements)
2
88
0
Order By: Relevance
“…Nevertheless, these findings are useful for four reasons. First, they support Holloway and Johnston's (1985) assertion that the current practice of group supervision is based on intuition and common sense. Second, and more important, the findings provide an empirical report of effective group supervision in one setting.…”
Section: Resultssupporting
confidence: 59%
“…Nevertheless, these findings are useful for four reasons. First, they support Holloway and Johnston's (1985) assertion that the current practice of group supervision is based on intuition and common sense. Second, and more important, the findings provide an empirical report of effective group supervision in one setting.…”
Section: Resultssupporting
confidence: 59%
“…That is, the SGS model provides a procedure for group supervision, rather than the frequent occurrence of one, primary supervisor who supervises trainees one at a time, in the context of a group meeting, while other group members passively observe this one-to-one interaction. Therefore, similar to Holloway and Johnston (1985). we believe group supervision, and the SGS model in particular, to be an effective use of available group time.…”
Section: Overview Of the Sgs Modelmentioning
confidence: 70%
“…Preliminary research on the model's effectiveness is also discussed. Holloway and Johnston (1985) indicated that research on the use of group formats to provide counseling supervision has declined in the last 10 years and that recent models have focused primarily on one-to-one supervision. Yet, they also stated that group supervision is practiced widely and that it is considered to be an economical use of supervisory time.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…field (Altfeld & Bernard, 1997;Borders, 1991;Carroll, 1996;Goodyear & Nelson, 1997;Holloway & Johnston, 1985;Proctor, 2000;Prieto, 1996Prieto, , 1998Proctor & Inskipp, 2001;Riva & Cornish, 1995;Stoltenberg, McNeill, & Delworth, 1998). Despite its wide use, few supervisors have received adequate training in group supervision techniques and practices.…”
mentioning
confidence: 99%